Vaginal and rectal microbiome changes following administration of a multi-species antenatal probiotic: A randomized control trial - Emily Malloy; Ashley E. Kates; Jonah Dixon; Colleen Riley; Nasia Safdar; Lisa Hanson (Gut Microbes Reports)
The gut and vaginal microbiome undergo changes during pregnancy which may be protective or harmful to the birthing person. Probiotics have been found to cause protective changes to the gut and vaginal microbiomes, with the potential to improve perinatal outcomes. This randomized control trial (NCT03696953) compares the vaginal and rectal microbiomes before and after an antenatal probiotic or placebo intervention, with a diverse group of pregnant people and a special focus on racial disparities. The vaginal and rectal microbiomes reveal non-significant increased Lactobacillus in the probiotics group, with a greater increase in participants who identified as Black. Potential implications and future studies are discussed.